1992
DOI: 10.2169/internalmedicine.31.516
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Common Bile Duct Stone with Cholangitis Presenting an Extraordinarily High Serum CA19-9 Value.

Abstract: A 63-year-old male complainined of right upper abdominal pain and jaundice. Laboratory data on admission showed hyperbilirubinemia, elevation of biliary enzymes and an extra ordinarily high value of serum CA19-9 (60,000 U/ml). Diagnostic imaging modalities including abdominal ultrasonogram, abdominal CT and PTC suggested a stone impaction of the common bile duct. Jaundice subsided after PTC-drainage in association with decreasing serum CA19-9 value, which returned to the normal level six weeks later. Spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Surprisingly, extremely elevated serum CA19-9 in patients with acute cholangitis like the reported case may occur [11]. Murohisa et al [11] presented a case of common bile duct stone with cholangitis and high serum CA 19-9 level (60,000 U/mL).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Surprisingly, extremely elevated serum CA19-9 in patients with acute cholangitis like the reported case may occur [11]. Murohisa et al [11] presented a case of common bile duct stone with cholangitis and high serum CA 19-9 level (60,000 U/mL).…”
Section: Discussionmentioning
confidence: 73%
“…Murohisa et al [11] presented a case of common bile duct stone with cholangitis and high serum CA 19-9 level (60,000 U/mL). Jaundice subsided after PTC-drainage in association with decreasing serum CA 19-9 value, which retuned to the normal level 6 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…12 Nevertheless, false-positive results owing to benign disease such as pancreatitis 13 or acute cholangitis have been reported. 14 In the current case, we diagnosed the liver mass as IPT because of spontaneous regression of the tumor size and reduction in serum CA19-9. The reasons for extreme elevation of the serum CA19-9 elevation in the current case are unclear.…”
mentioning
confidence: 79%
“…Moderately high serum levels of CA 19-9 can be detected during benign diseases of the liver, pancreas and biliary tract, but enormously high serum levels of CA 19-9 for these diseases were found in only a few cases, such as cirrhosis and acute cholangitis (16,19,20). The duration for normalization of elevated CA 19-9 level is varied.…”
Section: Discussionmentioning
confidence: 99%
“…A CA 19-9 value of >1,000 U/ml usually indicates a digestive cancer and has been reported to have a specificity over 99% for pancreatic cancer (16); nevertheless, falsepositive results owing to benign diseases such as pancreatitis or liver cirrhosis have been noted (17,18). Murohisa et al (19) reported a case of acute cholangitis with a CA 19-9 level of 6000 IU/ml, which had decreased in six weeks after successful biliary drainage.…”
Section: Introductionmentioning
confidence: 99%